Recurrence of orbital cysts in the branchio-oculo-facial syndrome. Issue 6 (June 1992) - Fielding, D W; Fryer, A E
Abstract : Two sibs with the branchio-oculo-facial syndrome are reported. They both have orbital haemangiomatous cysts, which is a previously unreported feature. Both parents are clinically normal and unrelated. This disorder has been reported showing autosomal dominant transmission so this family could represent either an autosomal recessive form or germline mosaicism for the dominant gene.